Jurysdykcja uniwersalna wobec zbrodniarzy syryjskich: Casus sądów niemieckich - Adamczyk, Anita (PRAWO i WIĘŹ, 2025)
The war in Syria has created one of the largest humanitarian crises in the 21st century. Syrian authorities have committed gross violations of humanitarian and human rights law during the conflict, which has influenced millions of Syrians to flee. Some stayed in neighboring countries, while others went to Europe. Among those who received international protection were not only victims, witnesses, but also perpetrators of crimes against humanity and war crimes committed in Syria. The paper posits that among the Syrian migrants seeking international protection in Europe were war criminals who, years later, were brought to justice in European states, a testimony to the breaking of the culture of impunity.